2016
DOI: 10.1097/md.0000000000005378
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and genetic discoveries of an intracranial mixed neuronal-glial tumor

Abstract: Background:Congenital intracranial tumors as a group are quite rare, representing only 0.5% to 1.5% of all pediatric brain neoplasms.Case report:We reported a case of congenital mixed neuronal-glial tumor detected by ultrasound at 30 weeks of gestation. It showed that the tumor was 2.5 × 2.3 × 2.1 cm3 in size, located in the sellar region, regular shape, and slightly heterogeneous solid mass with a little cystic component. No color flow was present inside the tumor, but the peripheral encirclement by arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Compared with the fetuses in the control group, the four-chambered hearts of the fetuses in the CoA group were more spherical, that is, the long diameter was shortened and the transverse diameter was increased, and the difference was statistically signi cant (P < 0.01) (Table 1); There was a statistically signi cant difference in the sphericity index of the left ventricular segment 18-24 (P < 0.05) (Table 2); there was a statistically signi cant difference in the spherical index of the right ventricular segment 8-11 (P < 0.05) (Table 3); Compared with the fetuses in the control group, there were signi cant differences in left ventricular fraction area change and longitudinal strain (P < 0.05); right ventricular fraction area change and longitudinal strain had no statistical difference (P > 0.05) (Table 4); compared with the control group, the left ventricular short-axis shortening rate FS 1-12 segments had statistical differences (P < 0.05) (Table 5); the right ventricular short-axis shortening rate FS 1-4 segments were signi cantly different (P < 0.05) (Table 6). [9][10][11][12][13] . Recent studies have shown that there are still great di culties in the accurate diagnosis of CoA in the fetal period.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the fetuses in the control group, the four-chambered hearts of the fetuses in the CoA group were more spherical, that is, the long diameter was shortened and the transverse diameter was increased, and the difference was statistically signi cant (P < 0.01) (Table 1); There was a statistically signi cant difference in the sphericity index of the left ventricular segment 18-24 (P < 0.05) (Table 2); there was a statistically signi cant difference in the spherical index of the right ventricular segment 8-11 (P < 0.05) (Table 3); Compared with the fetuses in the control group, there were signi cant differences in left ventricular fraction area change and longitudinal strain (P < 0.05); right ventricular fraction area change and longitudinal strain had no statistical difference (P > 0.05) (Table 4); compared with the control group, the left ventricular short-axis shortening rate FS 1-12 segments had statistical differences (P < 0.05) (Table 5); the right ventricular short-axis shortening rate FS 1-4 segments were signi cantly different (P < 0.05) (Table 6). [9][10][11][12][13] . Recent studies have shown that there are still great di culties in the accurate diagnosis of CoA in the fetal period.…”
Section: Resultsmentioning
confidence: 99%
“…At CD and PD, ICH shows no vascularization (10). But although conventional Doppler imaging techniques (CDIT) provides valuable data for evaluating BF, it does not disclose fine vessels and low velocity BF data.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the long-term growth process of nasal polyps, due to blocking the ostium of the sinuses or preventing the outflow of secretions from the ostium, it is easy to lead to the degeneration, necrosis or liquefaction of the inside of the sinuses or the polyps themselves due to bacterial infection, and finally form a purulent or mucopurulent abscess like substance. The creatine complex (Cr) contains creatine and phosphoric acid When the energy metabolism of creatine decreases, Cr increases, and the higher the peak value of Cr, the worse the metabolism of brain tissue; Lac is stored in the extracellular and intracellular space, mainly composed of two resonance peaks, which are also called double lines in medical circles; when TE is 288, the double peaks are upward, when TE is 144, the double peaks are downward [1][2][3][4][5][6][7] . In the healthy state, cells are mainly aerobic metabolism, Lac peak is trace or none; the growth block of nasal polyp tissue has an inhibitory effect on cell aerobic respiration, and glycolysis will be strengthened, so Lac peak is increased [6][7][8][9][10] .…”
Section: Spectrum Characteristicsmentioning
confidence: 99%
“…The creatine complex (Cr) contains creatine and phosphoric acid When the energy metabolism of creatine decreases, Cr increases, and the higher the peak value of Cr, the worse the metabolism of brain tissue; Lac is stored in the extracellular and intracellular space, mainly composed of two resonance peaks, which are also called double lines in medical circles; when TE is 288, the double peaks are upward, when TE is 144, the double peaks are downward [1][2][3][4][5][6][7] . In the healthy state, cells are mainly aerobic metabolism, Lac peak is trace or none; the growth block of nasal polyp tissue has an inhibitory effect on cell aerobic respiration, and glycolysis will be strengthened, so Lac peak is increased [6][7][8][9][10] . The degree of necrosis and degeneration of nasal polyps was in direct proportion to the decrease of NAA and the increase of Cho.…”
Section: Spectrum Characteristicsmentioning
confidence: 99%